Eugenic Sterilization: Medico-Legal and Sociological Aspects - Robinson, Felipe C. (1979)
The court-ordered sterilization of a normal 18-year-old black female in North Carolina focused attention on the unfortunate impact of eugenic statutes that allow sterilization as a method of social control. The existence of these laws in many states allows misapplication and abuse of authority which, not infrequently, is directed liberally to blacks and other minority groups. Eugenic sterilization is, at this time, a legally accepted form of “medical treatment.” The justification of such sterilization is the vague concept that the presumed “mentally deficient” individual is probably a potential parent of socially inadequate offspring who would likewise be socially inadequate. Since there never has been factual substantiation of whether the sterilization of these individuals will diminish the incidence of mental retardation, it is necessary to focus attention on the concept of eugenic sterilization and point out its many fallacies.